A new approach for development of vaccine against visceral leishmaniasis: Lipophosphoglycan and polyacrylic acid conjugates - Allahverdiyev, Adil M.; Koc, Rabia Cakir; Bagirova, Melahat; Elcicek, Serhat; Baydar, Serap Yesilkir; Oztel, Olga Nehir; Akdeste, Zeynep (Wolters Kluwer Medknow Publications, 2017)
Objective: To determine the antileishmanial vaccine effectiveness of lipophosphoglycan (LPG) and polyacrylic acids (PAA) conjugates on in vivo mice models. Methods: LPG molecule was isolated and purified from large-scale Leishmania donovani parasite culture. Protection efficacies of LPG alone, in combination with Freund's adjuvant, in a physical mixture and in conjugate (consisting of various LPG concentrations) with PAA, were comparatively determined by various techniques, such as cultivation with the micro-culture method, assessment of in vitro infection rates of peritoneal macrophages, determination of parasite load in liver with Leishman-Donovan Units, and detection of cytokine responses. Results: Obtained results demonstrated that the highest vaccine-mediated immune protection was provided by LPG-PAA conjugate due to all parameters investigated. According to the Leishman-Donovan Units results, the sharpest decline in parasite load was seen with a ratio of 81.17% when 35 mg LPG containing conjugate was applied. This value was 44.93% for the control group immunized only with LPG. Moreover, decreases in parasite load were 53.37%, 55.2% and 65.8% for the groups immunized with 10 mg LPG containing LPG-PAA conjugate, a physical mixture of the LPG-PAA, and a mixture of LPG + Freund's adjuvant, respectively. Furthermore, cytokine results supported that Th1 mediated protection occurred when mice were immunized with LPG-PAA conjugate. Conclusions: It has been demonstrated in this study that conjugate of LPG and PAA has an antileishmanial vaccine effect against visceral leishmaniasis. In this respect, the present study may lead to new vaccine approaches based on high immunogenic LPG molecule and adjuvant polymers in fighting against Leishmania infection.
Keywords: Leishmania; Lipophosphoglycan; Vaccine; Polymer; Polyacrylic acid